In the Guise of the Popular: the Deceptive Image of the Asàrotos Òikos Mosaics - Fathy, Ehud (Eikón / Imago, 2022)
The Roman asàrotos òikos (“Unswept Floor/Room”) mosaics, which were discovered in Italy and in Tunisia, and date from the end of the first to the sixth century AD, showcase a seemingly popular theme: scraps of food that had fallen (or were thrown) under the table during the banquet, colourfully displayed, appealing and appetising to the eyes. These mosaics are, in fact, Roman variations on a famous prototype created by Sosus in Hellenistic Pergamon, which was never discovered. The Roman mosaics reveal a unique tension between the display of impersonal, mundane reality in an illusory manner and the use of irony and disguised symbolism. The depiction of everyday life and elements that carry various symbolic meanings in trompe-l’œil prompts an interpretive reading of the artwork. The use of visual deception not only forms the ground for contemplative thought, but also enriches the reading by adding more layers of veiled meanings that need to be recognised and decoded by the viewers. This particular combination of aesthetics and iconography forms complex allegorical content. This article focuses on the asàrotos òikos mosaics which were discovered in Italy, and their particular combination of a popular theme, symbolism and illusionism.